Effects of compressing parameters and Mg(OH)2 content on mechanical properties and flame retardancy of rice straw-fibre reinforced composites - Doan Van Hong Thien; Thao Phuong Nguyen; Mong Linh Nguyen Thi; Ngoc Tuyet Tran; Thanh Nhan Le; Trung Nam Nguyen; Manh Can Le; Chanh-Nghiem Nguyen; Dan-Thuy Van-Pham (Vietnam Journal of Science, Technology and Engineering, 2021)
Rice straw fibre was utilized for fabricating unidirectional (UD) composites. In this study, the effects of compression temperature (160, 170, 180°C), duration (2, 5, 10, 15, and 20 min), pressure (100, 125, and 150 kg.cm-2), and fibre volume fraction (20, 30, 40, and 50%) on the mechanical properties of composites were investigated, respectively. The composite with optimal mechanical properties was prepared at a temperature of 180°C, pressure of 125 kg.cm-2 for 10 min, and at a fibre volume fraction of 40%. Mg(OH)2 was found to be an appropriate additive to enhance the flame retardancy of the composite. Interestingly, this agent also improved the mechanical and thermal insulation properties of the obtained composite at a ratio of 20% Mg(OH)2. The impact strength reached its highest value of 31.1 kJ.m-2, which is approximately 2.5 higher than that value at 10% and 30% Mg(OH)2, respectively. The 20% Mg(OH)2 added composite showed the best thermal insulation ability. The flame endurance of the specimen was rated as HB, V0, and 5VB standards.